Hematopoietic and Mesenchymal Stem Cells for the Treatment of Chronic Respiratory Diseases: Role of Plasticity and Heterogeneity. (19th January 2014) - Conese, Massimo; Piro, Donatella; Carbone, Annalucia; Castellani, Stefano; Di Gioia, Sante
Abstract : Chronic lung diseases, such as cystic fibrosis (CF), asthma, and chronic obstructive pulmonary disease (COPD) are incurable and represent a very high social burden. Stem cell-based treatment may represent a hope for the cure of these diseases. In this paper, we revise the overall knowledge about the plasticity and engraftment of exogenous marrow-derived stem cells into the lung, as well as their usefulness in lung repair and therapy of chronic lung diseases. The lung is easily accessible and the pathophysiology of these diseases is characterized by injury, inflammation, and eventually by remodeling of the airways. Bone marrow-derived stem cells, including hematopoietic stem/progenitor cells (HSPCs) and mesenchymal stromal (stem) cells (MSCs), encompass a wide array of cell subsets with different capacities of engraftment and injured tissue regenerating potential. Proof-of-principle that marrow cells administered locally may engraft and give rise to specialized epithelial cells has been given, but the efficiency of this conversion is too limited to give a therapeutic effect. Besides the identification of plasticity mechanisms, the characterization/isolation of the stem cell subpopulations represents a major challenge to improving the efficacy of transplantation protocols used in regenerative medicine for lung diseases.